دور التدقيق الداخلي في تطبيق الحوكمة بالمؤسسات الاقتصادية - علون, محمد لمين; بن خليفة, حمزة; صحراوي, فارس (جامعة الوادي - University of Eloued, 2019)
انّ وظيفة التّدقيق الدّاخلي عادة ما تخدم أطرافا تمارس دورا هاما في حوكمة المؤسسات مثل مجلس الإدارة، لجنة التّدقيق والتّدقيق الخارجي فإنّها تساهم في دعم الحوكمة. ومن أجل تفعيل دور التّدقيق الدّاخلي في تطبيق حوكمة المؤسسات وضمان تطوير وترقية الأداء العام للمؤسسة، بادر معهد المدققين الدّاخليين لتطوير المعايير الدّولية للتّدقيق الدّاخلي، لجعلها أداة قوية لإضافة قيمة للمؤسسة من خلال خدمات التّأكيد والاستشارة وتقييم وتدقيق الوظائف والأنشطة، ولقد تطوّر التدقيق الداخلي وأتسع نطاقه ليشمل تقييم المخاطر، والتّحقق من الإجراءات الرّقابية وإدخال تحسينات على أساليبها واختبارات مدى الالتزام بأخلاقيات وقواعد السلوك المهني، من أجل خدمة أصحاب المصالح ودعم ثقتهم في المعلومات المحاسبية اللّازمة لاتخاذ القرارات الإدارية والاستثمارية. Internal audit usually serves parties that play an important role in corporate governance such as board of directors, audit committee and external audit, which contribute in supporting governance. In order to activate the role of internal audit in applying corporate governance and to ensure the development and promotion of the institution's overall performance, the institute of internal auditors has developed the international standards of internal auditing, to be a powerful tool to add value to the institution through assurance and consultation service, auditing and evaluation of functions and activities. Internal audit has been developed and expanded to include risk assessment, control procedures verification and improving its methods and test the commitment to ethics and professional conduct, to serve stakeholders and support their trust in the accounting information needed for administrative and investment decision-making.
The Role Of Internal Audit In Applying Overnance In Economic Institutions
مقال
Keywords: التدقيق الداخلي، حوكمة المؤسسات، نظام الرقابة الداخلية، إدارة المخاطر، أخلاقيات وقواعد السلوك المهني.; Internal Audit, Corporate Governance, Internal Control System, Risk Management, Ethics and professional Conduct.